2014
DOI: 10.5539/ies.v7n11p173
|View full text |Cite
|
Sign up to set email alerts
|

Why Singaporean 8th Grade Students Gain Highest Mathematics Ranking in TIMSS (1999-2011)

Abstract: The international comparison of students' mathematics knowledge and competencies is an effective method of evaluating students' mathematics performance and developing policies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The language has become a problem that they face while planning the curriculum (Gopinathan, 2002). Also, there is an issue with the different abilities of the students and that develop three courses in secondary; Special/Express, Normal (Academic) and Normal (Technical) (Lessani, Yunus, Tarmiz, & Mahmud, 2014). In 1997, it was the start of developing creativity in schools (Gopinathan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The language has become a problem that they face while planning the curriculum (Gopinathan, 2002). Also, there is an issue with the different abilities of the students and that develop three courses in secondary; Special/Express, Normal (Academic) and Normal (Technical) (Lessani, Yunus, Tarmiz, & Mahmud, 2014). In 1997, it was the start of developing creativity in schools (Gopinathan, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…565-569). If this is the case, it is understandable that certain researchers are interested in analysing the differences between textbooks from different countries as a way to investigate the curriculum as (potentially) implemented in those countries (e.g., Erbas, Alacaci & Bulut, 2012;Lessani, Yunus, Tarmiz & Mahmud, 2014;Mayer et al, 1995).…”
Section: Word Problem Solving In Mathematics Textbooksmentioning
confidence: 99%
“…In Indonesia, remodeling textbooks to make them more appropriate and meet the applicable standards is one way to upgrade the education quality. Furthermore, Lessani, Yunus, Tarmiz, and Mahmud (2014) stated that students' knowledge and competence should be compared to other students from different countries to evaluate their performance and improve their achievement in science and mathematics at various levels of education. On the other hand, Mailizar, Alafaleq, & Fan (2014) revealed that to improve the quality of student learning in any education system, the government has to pay attention to the curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current textbook analysis research focused on the textbook's content, structure, and expectation (O'Keeffe & O'Donoghue, 2015). Lessani et al (2014) Other research focused on particular mathematics topics, for example, the concept of proportion (Dole & Shield, 2008) and the concept of function (Mesa, 2004). Lianghuo Fan, Mailizar, Alafaleq, and Wang (2018) also presented a comparative analysis of textbook content, focusing on how geometric proofs are conveyed in secondary school mathematics textbooks in China, Indonesia, and Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%